The health communication for the acceleration of stunting reduction in Garut regency - Suminar, Jenny Ratna; Prasanti, Ditha; Fuady, Ikhsan; Arifin, Hadi Suprapto; Aisha, Sarah (Universitas Padjadjaran, 2023)
Background: The stunting prevalence rate is still a significant concern that must be resolved in Indonesia, especially in West Java. The latest data obtained from SSGI (2022) states that out of 27 districts/cities in West Java, four districts/cities have a high stunting prevalence (30%-39.9%) which are Garut Regency, Cianjur Regency, Bandung Regency, and Cirebon City. Garut is in the public spotlight because it has the highest stunting prevalence in West Java. Purpose: Therefore, referring to these data, researchers are interested in knowing the health communication polemic in responding to Garut Regency’s acceleration of reducing stunting prevalence. Method: The research approach used is qualitative research with a case study method. In Garut, stunting is a critical issue and is still being worked on. This study used in-depth interviews to collect data from five informants, participatory observation, and a literature study. Results: The results of the study showed exciting findings, including First, the existence of social, cultural, and economic factors as the cause of the health communication polemic in the acceleration of reducing Garut Regency’s stunting prevalence; Secondly, the health communication process has been conducted to accelerate a stunting reduction in Garut Regency; and thirdly, the need for health communication planning evaluation for accelerating stunting reduction so that even this has become a polemic until now. Conclusion: The health communication program planning evaluation carried out should be able to determine the next steps that must be taken so that this health communication polemic can be resolved immediately. Implications: The findings from this research have implications for the development of the next accelerated stunting reduction program, especially in Garut. The existence of an evaluation of the communication program is an important note that can be considered to realize the achievement of Indonesia Emas 2024.